The Effect of Employee Engagement, Individual Characteristics and Communication on the Performance - Suwandi Suwandi; Dwi Astuti; Siska Prisilia (PT Mattawang Mediatama Solution, 2024)
This research examines the effect of employee engagement, individual characteristics, and communication on the performance of village office employees in Cikarang Utara District. Using a quantitative approach with explanatory research, data were collected through observation, literature study, and questionnaires distributed to all employees of three village offices. The analysis was carried out using descriptive analysis and Structural Equation Modeling (SEM). The results indicate that employee engagement, individual characteristics, and communication have a positive and significant effect on employee performance. Among these three factors, communication has the strongest influence on employee performance. Effective communication within the organization facilitates information delivery, aligns goals, and enables smooth coordination, ultimately enhancing employee productivity and performance. This study highlights the importance of fostering employee engagement, considering individual characteristics, and establishing effective communication channels to improve the performance of village office employees and optimize public services.